Injectable piezoelectric conductive hydrogel as well as preparation method and application thereof
By uniformly distributing SrTiO3 piezoelectric nanoparticles in injectable conductive hydrogels, the problems of piezoelectric materials aggregation and poor conductivity in hydrogels are solved, efficient piezoelectric effect and electrical signal transmission are achieved, and wound healing is promoted .
Patent Information
- Application Number
- CN202411628600.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
Existing piezoelectric materials are prone to agglomeration in hydrogels, resulting in suppression of piezoelectric effect. At the same time, poor conductivity of the hydrogel hinders the transmission of electrical signals and limits its application in wound healing.
By evenly distributing SrTiO3 piezoelectric nanoparticles in the spatial framework of injectable conductive hydrogels, the nanoparticles are fixed by using coordination bonds to improve the conductivity and piezoelectric effect of the hydrogel.
The uniform distribution of piezoelectric nanomaterials in the hydrogel is achieved, which ensures the efficient piezoelectricity of the hydrogel, and promotes the transmission of electrical signals by improving conductivity and promotes wound healing.
Smart Images

Figure CN119488630A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to an injectable piezoelectric conductive hydrogel and a preparation method and application thereof. Background Art
[0002] As the largest organ in the human body, the skin has the potential immune system function of protecting the body from microorganisms and maintaining homeostasis. However, the skin is always vulnerable to damage from various external factors, causing wounds. If it cannot be repaired in time, it will cause wound ulcers and infections, which will seriously threaten human health. Wound healing is a long, complex and dynamic process, including four stages: hemostasis, inflammation, proliferation and remodeling. At present, a large number of materials are used to accelerate wound healing, such as carbon materials, metal oxide materials, precious metal nanomaterials, etc.
[0003] However, accelerating a single stage of wound healing is ineffective for the multi-stage process of wound healing. When the skin is injured, endogenous electric fields and currents are spontaneously established by the difference in transepithelial potential of the damaged epithelial barrier and maintained until the wound healing process is completed. Inspired by this naturally occurring endogenous electric field and current, electrotherapy is used to accelerate the healing of skin wounds. Electrical stimulation can promote the production of platelet-derived microparticles and the activation of procoagulant markers on the platelet surface during the hemostasis phase, enhance the phagocytic ability of macrophages during the inflammatory phase, and stimulate keratinocyte proliferation and differentiation, increasing keratin deposition and keratinocyte migration rate during the proliferation phase. Even during the remodeling phase, electrical stimulation can still increase the contractility of myofibroblasts and the replacement of type III collagen, and enhance maturity by increasing tensile strength. Obviously, electrotherapy is emerging as an effective strategy to promote wound healing by mimicking naturally occurring endogenous electric fields and currents. However, the remarkable effects of electrotherapy have not led to its widespread application in clinical practice, because the large size of the external power source hinders clinical use due to its high cost, inconvenience, non-wearable, non-real-time, and almost non-portable nature. Therefore, providing exogenous electric fields and currents at the wound site without any external electrical equipment could enable widespread clinical application of electrotherapy for wound healing.
[0004] Piezoelectric materials have unique mechanical-electrical energy conversion capabilities, making them very attractive for wound healing. In their original state, the charge centers of anions and cations of piezoelectric materials coincide. When subjected to mechanical deformation by external force, the distance between the negative and positive charges changes, causing the centers of negative and positive charges to be dislocated, releasing sustained piezoelectricity. The biomedical applications of piezoelectric materials have the potential to avoid the use of auxiliary and external electrical devices to induce electrical stimulation. To date, many piezoelectric materials have been used to generate weak electricity to promote wound healing, but piezoelectric materials themselves do not have a moisture environment suitable for wound healing, and are prone to stick to wounds, which may cause re-injury. Based on this challenge, people consider incorporating piezoelectric materials into hydrogels, which not only meets the moist healing environment, but also effectively reduces secondary laceration trauma caused by traditional dry dressings adhering to the wound surface. However, on the one hand, due to their heavy weight and lack of interaction with the hydrogel scaffold, piezoelectric nanomaterials tend to agglomerate within the hydrogel matrix, severely inhibiting the piezoelectric effect; on the other hand, the poor conductivity of hydrogels hinders the effective transfer of electrons from piezoelectric nanomaterials to cells or tissues through the hydrogel matrix, which also inhibits the piezoelectric effect.
[0005] Therefore, in order to maintain a stable piezoelectric current to electrically stimulate wound tissue, the hydrogel must have excellent conductivity to facilitate the transmission of electrical signals. In addition, after injectable hydrogels are injected into wounds in the form of solutions, they can fill irregular or deeper wounds and form gels in situ, which is easy to operate and less invasive to the skin and surrounding tissues. Therefore, the injectability of hydrogels also shows unique advantages in wound healing. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide an injectable piezoelectric conductive hydrogel.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: SrTiO3 piezoelectric nanoparticles are uniformly distributed in the space skeleton of the injectable conductive hydrogel PG through coordination bonds;
[0010] The titanium on the surface of the SrTiO3 piezoelectric nanoparticles coordinates with the carboxyl group of the injectable conductive hydrogel PG.
[0011] As a preferred embodiment of the injectable piezoelectric conductive hydrogel of the present invention, the mass doping ratio of SrTiO3 piezoelectric nanoparticles to the injectable conductive hydrogel PG in the system of the injectable piezoelectric conductive hydrogel is 1:80-100.
[0012] Another object of the present invention is to provide a method for preparing injectable piezoelectric conductive hydrogel.
[0013] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0014] 1-4 g of gelatin and 0.4 g of 3-amino-4-methoxybenzoic acid powder are added to 10 mL of deionized water, and then 0.546 g of ammonium persulfate is added thereto to perform polymerization reaction to obtain a mixed solution;
[0015] The mixed solution is dialyzed using a dialysis bag with a molecular weight cutoff of 1200 to 1400 Daltons, and the dialyzed solution is freeze-dried to obtain a conductive hydrogel precursor;
[0016] 20 μL of an aqueous solution of SrTiO3 nanoparticles with a concentration of 1 to 3 mg / mL is mixed with 1 to 2.5 μL of N-hydroxysuccinimide with a concentration of 24 mmol / L to obtain a mixed solution I;
[0017] 500-800 μL of the conductive hydrogel precursor and 1-5 μL of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride having a concentration of 48 mmol / L are mixed to obtain a mixed solution II;
[0018] The mixed solution I and the mixed solution II are quickly mixed to form an injectable piezoelectric conductive hydrogel.
[0019] As a preferred embodiment of the method for preparing the injectable piezoelectric conductive hydrogel of the present invention, the method for preparing the SrTiO3 piezoelectric nanoparticles comprises:
[0020] 2.43 g of strontium hydroxide octahydrate was added to 80 mL of deionized water, and ultrasonicated until completely dissolved. Then, 0.8 to 1 mL of titanium tetrachloride and 100 to 500 μL of anhydrous ethanol solution were added while stirring. Then, 5 g of sodium hydroxide was added to the solution while stirring until it was completely dissolved and cooled to room temperature.
[0021] The solution was then transferred to a reactor with a volume of 100 mL for high-temperature hydrothermal reaction. The obtained product was washed with anhydrous ethanol and dried to obtain SrTiO3 nanoparticles.
[0022] As a preferred embodiment of the method for preparing the injectable piezoelectric conductive hydrogel of the present invention, the polymerization reaction is carried out in a water bath at 50 to 55° C. for 24 to 26 hours.
[0023] As a preferred embodiment of the method for preparing the injectable piezoelectric conductive hydrogel of the present invention, the dialysis is performed by water bath dialysis at 50 to 60° C. for 24 to 48 hours.
[0024] As a preferred embodiment of the method for preparing the injectable piezoelectric conductive hydrogel of the present invention, the reaction temperature of the high-temperature hydrothermal reaction is 240-250° C., and the reaction time is 48-50 h.
[0025] As a preferred embodiment of the method for preparing the injectable piezoelectric conductive hydrogel of the present invention, the drying temperature is 30-60°C.
[0026] Another object of the present invention is to provide an injectable piezoelectric conductive hydrogel for use in wound repair.
[0027] In order to solve the above technical problems, the present invention provides the following technical solution: injecting the injectable piezoelectric conductive hydrogel into the wound, stimulating the migration and proliferation of epidermal fibroblasts through the micro-electricity generated by the movement, and promoting wound healing.
[0028] Beneficial effects of the present invention:
[0029] The injectable piezoelectric conductive hydrogel of the present invention can evenly distribute piezoelectric nanomaterials in the conductive hydrogel space skeleton. Compared with the prior art, nanomaterials are not easily agglomerated, thereby ensuring the piezoelectric efficiency of the hydrogel. Compared with the prior art, the conductivity of the hydrogel ensures the effective transfer of current from the nanomaterial to the surface of the hydrogel, promoting cell migration and proliferation. It is injected into the wound of mice, and the hydrogel is squeezed by the movement of the mice, and the electrical stimulation generated promotes wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0031] Figure 1 Transmission electron microscopy image of SrTiO3 nanoparticles prepared in Example 1 of the present invention.
[0032] Figure 2 This is the X-ray diffraction pattern of the SrTiO3 nanoparticles prepared in Example 1 of the present invention.
[0033] Figure 3This is a scanning electron microscope image of the injectable piezoelectric conductive hydrogel (SPG) prepared in Example 1 of the present invention.
[0034] Figure 4 This is a schematic diagram of the principle of generating micro-electricity through the movement of the injectable piezoelectric conductive hydrogel prepared in Example 1 of the present invention.
[0035] Figure 5 This is a scanning electron microscope image of the conductive hydrogel (PG) prepared in Comparative Example 1 of the present invention.
[0036] Figure 6 This is the piezoelectric and conductivity test results of the hydrogel.
[0037] Figure 7 This is a graph showing the test results of the hydrogel's tissue adhesion performance.
[0038] Figure 8 Figure 2 shows the experimental results of the biosafety of the hydrogel.
[0039] Fig. 9 Experimental diagram of hydrogel stimulating cell migration.
[0040] Fig.10 This is a diagram showing the experimental results of using hydrogel to repair mouse wounds. DETAILED DESCRIPTION
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0044] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0045] Example 1
[0046] This embodiment provides a method for preparing an injectable piezoelectric conductive hydrogel, specifically:
[0047] 1) Preparation of SrTiO3 nanoparticles:
[0048] 2.43 g of strontium hydroxide octahydrate was added to 80 ml of deionized water, and ultrasonicated until completely dissolved. Then, 0.8-1 ml of titanium tetrachloride and 100-500 μL of anhydrous ethanol solution were added while stirring. Then, 5 g of sodium hydroxide was added to the solution while stirring until it was completely dissolved and cooled to room temperature.
[0049] Then the solution was transferred to a 100 ml reactor and reacted at 240-250° C. for 48-50 h. The obtained product was washed three times with anhydrous ethanol and dried in an oven at 60° C. to obtain SrTiO3 nanoparticles.
[0050] Figure 1 This is a transmission electron microscope image of the SrTiO3 nanoparticles prepared in this step. Figure 1 a is a transmission electron microscopy image, showing that the SrTiO3 nanoparticles have a cubic morphology and an average size of about 122nm; Figure 1 b is the energy dispersive X-ray spectrum, which shows that SrTiO3 nanoparticles are composed of Sr, Ti and O elements and are uniformly distributed. Figure 2 The X-ray diffraction pattern of SrTiO3 nanoparticles shows that the crystal structure of SrTiO3 nanoparticles corresponds to the perovskite crystal structure (PDF#35-0734) and has clear diffraction peaks at (100), (110), (111), (200), (210), (211), (220) and (310).
[0051] 2) Preparation of injectable piezoelectric conductive hydrogel:
[0052] 4 g of gelatin and 0.4 g of 3-amino-4-methoxybenzoic acid powder were added to 10 mL of deionized water, and 0.546 g of ammonium persulfate was added thereto to initiate polymerization of 3-amino-4-methoxybenzoic acid. The polymerization reaction was carried out in a water bath at 50° C. for 24 h to obtain a mixed solution.
[0053] The mixed solution was then dialyzed in a dialysis bag with a molecular weight cutoff of 1200 to 1400 Daltons in a 50°C water bath for 24 h, and the dialyzed solution was freeze-dried to obtain a conductive hydrogel precursor;
[0054] 20 μL of an aqueous solution of SrTiO3 nanoparticles with a concentration of 1 to 3 mg / mL is mixed with 1 to 2.5 μL of N-hydroxysuccinimide with a concentration of 24 mmol / L to obtain a mixed solution I;
[0055] 500-800 μL of the conductive hydrogel precursor and 1-5 μL of 48 mmol / L 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride are mixed to obtain a mixed solution II;
[0056] The mixed solution I and the mixed solution II are quickly mixed to form a piezoelectric hydrogel, which is the injectable piezoelectric conductive hydrogel (SPG) of this embodiment.
[0057] Figure 3 is a scanning electron microscope image of the injectable piezoelectric conductive hydrogel (SPG) prepared in this embodiment, Figure 4 The schematic diagram of the micro-electricity generated by its movement. Its working principle is that when the piezoelectric hydrogel is injected into the wound of the mouse, the hydrogel can fit the wound completely according to the irregular wound, forming a gel that sticks tightly to the wound. When the mouse moves, the SrTiO3 nanoparticles are squeezed, generating voltage and current, which are transmitted to the wound through the conductive hydrogel. Under the stimulation of microcurrent, the phosphorylation of phosphatidylinositol 3-kinase of fibroblasts is activated, which in turn activates the phosphorylation of protein kinase B, and finally induces the migration and proliferation of fibroblasts, promoting wound healing.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing a conductive hydrogel, specifically:
[0060] 1-4 g of gelatin and 0.4 g of 3-amino-4-methoxybenzoic acid powder are added to 10 mL of deionized water, and then 0.546 g of ammonium persulfate is added thereto to initiate polymerization of 3-amino-4-methoxybenzoic acid. The polymerization reaction is reacted in a water bath at 50-55° C. for 24-26 hours to obtain a mixed solution;
[0061] The mixed solution is then dialyzed in a dialysis bag with a molecular weight cutoff of 1200 to 1400 Daltons in a water bath at 50 to 60°C for 24 to 48 hours, and the dialyzed solution is freeze-dried to obtain a conductive hydrogel precursor;
[0062] Take 4 g of freeze-dried hydrogel precursor and dissolve it in 10 mL of PBS, adjust the pH value to 7.0, then take 500-800 μL of conductive hydrogel precursor, add 1-5 μL of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride with a concentration of 48 mmol / L and 1-2.5 μL of N-hydroxysuccinimide with a concentration of 24 mmol / L, and mix to form a conductive hydrogel (PG).
[0063] Figure 5 This is a scanning electron microscope image of the hydrogel prepared in this step, which shows that the conductive hydrogel prepared in this comparative example has a porous structure.
[0064] Example 2
[0065] This example conducts application tests on the hydrogels prepared in Example 1 and Comparative Example 1, specifically:
[0066] Piezoelectric and conductivity testing
[0067] 400 μL of hydrogel was dropped between two electrodes to form a hydrogel with a thickness of about 0.1 cm. Then the electrodes were fixed on human fingers to stimulate the generation of current by bending the fingers. The electrical signals were collected during the movement of human fingers. When the fingers were repeatedly bent and restored at a frequency of 1 Hz, the hydrogel deformed, generating voltage and current. The output voltage and current were measured by a 2400 measuring instrument.
[0068] The hydrogel was placed in the middle position of the two probes with a distance of 1 cm. The conductivity of the hydrogel was measured by a 2400 measuring instrument (measured in S / cm) and calculated as 1 / (2πDR), where D is the distance between the probes (cm), R=V / I, where I is the supply current (mA), and V is the corresponding voltage (mV). In order to further measure the conductivity of the hydrogel, a hydrogel with a length of 1 cm and a diameter of 0.5 cm was connected in series in the circuit, and the conductivity was detected using the light emitted by the LED.
[0069] Figure 6 The results of piezoelectric, conductive, and injectable hydrogels are shown in Figure 1; a is the conductivity of gelatin, PG hydrogel, and SPG hydrogel; b is the output voltage and current of the bent SPG hydrogel; and c is the output voltage and current of the SPG hydrogel fixed on the finger by bending the finger. The results show that micro-electricity can be generated by bending the SPG hydrogel or fixing the SPG hydrogel on the finger and bending the finger.
[0070] Tissue Adhesion Test
[0071] Drop 100 μL of hydrogel between two pieces of fresh mouse skin so that the contact area between the two pieces of fresh skin is 2.25 cm 2 , then clamp it on the tensile tester and draw a force-displacement curve based on the tensile displacement and tension;
[0072] The hydrogel was dropped onto fresh pig skin. After the hydrogel solidified and adhered to the pig skin, the adhesion of the hydrogel to the fresh pig skin was tested by repeated bending.
[0073] Figure 7are the results of tissue adhesion performance; a is the result of SPG hydrogel adhesion on fresh pig skin, b is the result of different hydrogels adhesion on mouse skin, c is the result of different hydrogels adhesion on mouse skin stretching, the results show that SPG hydrogel can stick tightly to pig skin, even under continuous bending, the liquid will not fall off the tissue, indicating that SPG hydrogel has the function of sealing wounds; b is the result of different hydrogels adhesion on mouse skin, indicating that SPG hydrogel has the ability to resist tensile destructive force; c is the result of different hydrogels adhesion on mouse skin stretching, indicating that SPG and PG hydrogels have strong adhesion.
[0074] Biosafety Testing
[0075] 400 μL of hydrogel was injected into a 6-well plate and waited for 1 to 3 min for the hydrogel to solidify into a gel. Then 1.6×10 5 Mouse embryonic fibroblasts (NIH-3T3) were cultured for 12 hours. Then, each well was sonicated at a frequency of 50 Hz for 5 minutes and then cultured for another 12 hours. The supernatant in the 6-well plate was then aspirated, washed three times with phosphate buffer, and then Calcein-AM / PI live and dead cell stain was added to the well plate for staining for 15 minutes. The cells were then washed three times with phosphate buffer, and fluorescent photos of the live and dead cells were taken using a Nikon inverted fluorescence microscope.
[0076] Figure 8 This is a diagram of the experimental results of biosafety, and the results show that under ultrasound, SPG hydrogel, PG hydrogel and SrTiO3 nanoparticles have very low cytotoxicity to NIH-3T3 cells.
[0077] Hydrogel-stimulated cell migration assay
[0078] 400 μL of hydrogel was injected into a 6-well plate and waited for 1 to 3 min for the hydrogel to solidify into a gel. Then 1.6×10 5 Mouse embryonic fibroblasts (NIH-3T3) were cultured for 12 hours. Then, each well was ultrasonicated at a frequency of 50 Hz for 5 minutes and then cultured for another 12 hours. The results of cell proliferation were detected by flow cytometry;
[0079] For the study of the expression of proteins related to cell migration stimulated by electrical signals, NIH-3T3 cells were obtained by the same method as above, and then the cells were lysed on ice with cell lysis buffer, and the cell lysis supernatant was collected by centrifugation. 1× protein loading buffer was added to the cell supernatant and boiled in boiling water for 5 minutes, and then used with a 12% SDS-polyacrylamide gel. After electrophoresis, transfer, blocking, incubation, and development, the expression of protein expression was detected using a chemiluminescence developer.
[0080] Fig. 9 This is an experimental diagram of hydrogel stimulating cell migration. The results show that under ultrasound, SPG hydrogel and SrTiO3 nanoparticles can significantly increase the expression of pPI3K protein and pAkt protein compared with PG hydrogel and PBS.
[0081] For mouse wound repair experiments
[0082] Balb / c female mice weighing 18-20 g and aged 4-6 weeks were shaved, and then injected with anesthetics according to the body weight of the mice in accordance with the requirements approved by the Animal Ethics Committee.
[0083] A: Mice were anesthetized and wounds were made on their backs. Then the injectable piezoelectric conductive hydrogel prepared in Example 1 was applied between electrodes and fixed on the wound. A 2400 measuring instrument was connected to the wound area. Once the mice regained consciousness and began to move, the changes in the body surface current were measured and recorded.
[0084] B: The mouse was anesthetized, and a wound of 1 cm in length was cut on the back with a scalpel. 50 μL of the injectable piezoelectric conductive hydrogel prepared in Example 1 was dripped on the wound. Then, the wound edges were pressed from both sides with fingers for 1 min to remove excess hydrogel. The length of the wound on the back of the mouse was measured and recorded with a vernier caliper every day.
[0085] Fig.10 This is an experimental result diagram of the repair of mouse wounds. The results show that movement can activate piezoelectric injectable hydrogel to generate micro-electricity, promoting wound healing, and its healing effect is better than that of the PBS treatment group.
[0086] Comparative Example 2
[0087] This comparative example attempts to use SrTiO3 nanoparticles alone for wound healing, but preliminary experimental results show that on the one hand, the particles cannot adhere to the wound and are easy to fall off, and on the other hand, the nanoparticles cannot be squeezed on the wound to generate microelectricity;
[0088] The nanoparticles are further pressed into tablets. The pressed nanoparticles can generate micro-electricity, but it is difficult to fix them on the wound.
[0089] Comparative Example 3
[0090] The difference between this comparative example and Example 1 is that the conductive gel PG is replaced by PDMS gel. Preliminary experimental results show that although it can generate micro-electricity under squeezing, it is difficult to achieve wound healing.
[0091] In addition, the study also found that the doping ratio of SrTiO3 nanoparticles compared to PG will also significantly affect the effect of the prepared SPG. If the SrTiO3 ratio is low, the micro-electricity it generates is too weak to promote wound healing, while if the ratio is higher than the present invention, it is easy to agglomerate, which will also lead to a decrease in micro-electricity.
[0092] In summary, the present invention discloses an injectable piezoelectric conductive hydrogel and a preparation method and application thereof. The injectable piezoelectric conductive hydrogel of the present invention is prepared by forming spatial coordination between piezoelectric nanoparticles and conductive hydrogel through metal and skeleton, and uniformly fixing piezoelectric nanoparticles in the spatial structure of conductive hydrogel. When the injectable piezoelectric conductive hydrogel is injected into the wound surface of a mouse wound, the hydrogel can completely fit the wound according to the irregular wound, forming a gel that is tightly attached to the wound. When the mouse moves, the piezoelectric nanoparticles are squeezed, generating voltage and current, and the current is transmitted to the hydrogel surface and the wound through the conductive hydrogel skeleton. Under the stimulation of microcurrent, the phosphorylation of phosphatidylinositol 3-kinase of fibroblasts is activated, and then the phosphorylation of protein kinase B is activated, and finally the migration and proliferation of fibroblasts are induced, promoting wound healing.
[0093] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An injectable piezoelectric conductive hydrogel, characterized in that: It is obtained by uniformly distributing SrTiO3 piezoelectric nanoparticles in the space skeleton of injectable conductive hydrogel PG through coordination bonds; The titanium on the surface of the SrTiO3 piezoelectric nanoparticles coordinates with the carboxyl group of the injectable conductive hydrogel PG.
2. The injectable piezoelectric conductive hydrogel according to claim 1, characterized in that: In the injectable piezoelectric conductive hydrogel system, the mass doping ratio of SrTiO3 piezoelectric nanoparticles to the injectable conductive hydrogel PG is 1:80-100.
3. The method for preparing the injectable piezoelectric conductive hydrogel according to any one of claims 1 or 2, characterized in that: include, 1-4 g of gelatin and 0.4 g of 3-amino-4-methoxybenzoic acid powder are added to 10 mL of deionized water, and then 0.546 g of ammonium persulfate is added thereto to perform polymerization reaction to obtain a mixed solution; The mixed solution is dialyzed using a dialysis bag with a molecular weight cutoff of 1200 to 1400 Daltons, and the dialyzed solution is freeze-dried to obtain a conductive hydrogel precursor; 20 μL of an aqueous solution of SrTiO3 nanoparticles with a concentration of 1 to 3 mg / mL is mixed with 1 to 2.5 μL of N-hydroxysuccinimide with a concentration of 24 mmol / L to obtain a mixed solution I; 500-800 μL of the conductive hydrogel precursor and 1-5 μL of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride having a concentration of 48 mmol / L are mixed to obtain a mixed solution II; The mixed solution I and the mixed solution II are quickly mixed to form an injectable piezoelectric conductive hydrogel.
4. The method for preparing the injectable piezoelectric conductive hydrogel according to claim 3, characterized in that: The method for preparing the SrTiO3 piezoelectric nanoparticles comprises: 2.43 g of strontium hydroxide octahydrate was added to 80 mL of deionized water, and ultrasonicated until completely dissolved. Then, 0.8 to 1 mL of titanium tetrachloride and 100 to 500 μL of anhydrous ethanol solution were added while stirring. Then, 5 g of sodium hydroxide was added to the solution while stirring until it was completely dissolved and cooled to room temperature. The solution was then transferred to a reactor with a volume of 100 mL for high-temperature hydrothermal reaction. The obtained product was washed with anhydrous ethanol and dried to obtain SrTiO3 nanoparticles.
5. The method for preparing the injectable piezoelectric conductive hydrogel according to claim 3, characterized in that: The polymerization reaction is carried out in a water bath at 50-55° C. for 24-26 hours.
6. The method for preparing the injectable piezoelectric conductive hydrogel according to claim 3, characterized in that: The dialysis is performed in a water bath at 50 to 60° C. for 24 to 48 hours.
7. The method for preparing the injectable piezoelectric conductive hydrogel according to claim 4, characterized in that: The reaction temperature of the high temperature hydrothermal reaction is 240-250° C., and the reaction time is 48-50 hours.
8. The method for preparing the injectable piezoelectric conductive hydrogel according to claim 4, characterized in that: The drying temperature is 30-60°C.
9. Use of the injectable piezoelectric conductive hydrogel as claimed in claim 1 in wound repair.
10. The use of the injectable piezoelectric conductive hydrogel in wound repair as claimed in claim 4, characterized in that: The injectable piezoelectric conductive hydrogel is injected into the wound, and the micro-electricity generated by the movement stimulates the migration and proliferation of epidermal fibroblasts, thereby promoting wound healing.
Citation Information
Cited By
Heterojunction-enhanced injectable piezoelectric hydrogel as well as preparation method and application thereof
CN121338094A